2009
DOI: 10.4081/811
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of essential oils in relation to root differentiation in Angelica archangelica L.

Abstract: The accumulation of essential oils in Angelica archangelica subsp. archangelica roots at different developmental stages was investigated through histochemical and chemical analyses. Roots less than 1 mm in diameter showed a primary diarch structure and two primary secretory ducts in the pericycle. These ducts were ephemeral and probably became dysfunctional early on. Oil accumulation was observed only in the secondary secretory ducts formed by cambium activity and located in the secondary phloem. Gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…A. acutiloba is traditionally used to treat gynecological diseases and anemia [ 15 ]. Angelica archangelica is commonly used in traditional medicine to cure nervousness, insomnia, stomach and intestinal disturbances, skin diseases, respiratory problems, and arthritis [ 16 , 17 ]. Angelica glauca has been used to treat bilious complaints, infantile atrophy, and constipation [ 18 ].…”
Section: Traditional Uses Of Angelica Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A. acutiloba is traditionally used to treat gynecological diseases and anemia [ 15 ]. Angelica archangelica is commonly used in traditional medicine to cure nervousness, insomnia, stomach and intestinal disturbances, skin diseases, respiratory problems, and arthritis [ 16 , 17 ]. Angelica glauca has been used to treat bilious complaints, infantile atrophy, and constipation [ 18 ].…”
Section: Traditional Uses Of Angelica Speciesmentioning
confidence: 99%
“…Further, the authors reported that the composition of EOs varied greatly with the altitude of collection. Pasqua et al [ 16 ] investigated the accumulation of EOs in the roots of A. archangelica subsp. archangelica at different developmental stages.…”
Section: The Chemical Composition Of Essential Oils Of Amentioning
confidence: 99%
“…The efficacy of antimicrobial action of oils and extracts depends to a great degree on the chemical composition, which is connected with the type of oily plants, the growth conditions, harvesting, and processing, as well as the manner of obtaining the extracts. Differences in the chemical composition and biological activity were observed in garlic oils containing sulphur compounds [ 4 , 5 , 6 , 7 ], nettle [ 8 , 9 , 10 ], and chamomile [ 11 ], which contain biogenic amines and angelica-containing coumarins [ 12 , 13 , 14 ]. Furthermore, what is also significant is the qualitative-quantitative composition of various chemical compounds found in essential oils, since it is responsible for their antimicrobial efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the general assumption that undifferentiated in vitro cultures, except for a few well-known exceptions (e.g., taxanes, Yukimune et al, 1996), often lose the capacity to produce the secondary metabolites normally synthesized in plant. In some cases, this is due to a lack of specialized cells or secretory structures (St-Pierre et al, 1999 andPasqua et al, 2003). Indeed, the existence of a relationship between differentiation/ organization and secondary product formation in vitro has been well documented (Robins et al, 1991 andBiondi et al, 2002).…”
Section: Callus Formation (%)mentioning
confidence: 99%